PENGEMBANGAN MULTIMEDIA INTERAKTIF DISERTAI DRILLS PADA POKOK BAHASAN TEKANAN DI SMP - Hikma Yanti; Sri Wahyuni; Maryani Maryani; Pramudya Dwi Aristya Putra (FKIP Universitas Jember, 2017)
This research aimed to describe validation and effectiveness of interactivemultimedia and students’ response after the learning process was using interactivemultimedia accompanied drills on the subjects of pressure. This research includedresearch development to produce a product of media learning namely interactivemultimedia accompanied drills on the subjects of pressure in junior high schoolstudents. The development model used the Four-D (Define, Design, Develop, andDisseminate) model. The result of this research showed that assessments validator tointeractive multimedia was perfectly valid with the acquisition the percentage was88,65 %. In the developmental testing known that interactive multimedia was veryeffective used to improve students’ learning outcomes with the acquisition N-gain testwas 0,715 with was in the high category. In addition, the students’ response toward theinteractive multimedia had a positive and good response with the acquisition thepercentage of 87,95 %.Key word: interactive multimedia, drills, effectiveness, students’ response.